Association of mortality with fludrocortisone addition to hydrocortisone treatment among septic shock patients: a propensity score matching analysis - Cheng, Xiaoxiao; Fu, Zhiqin; Liu, Yiting; Zheng, Xiaoyu; Hu, Tianyang (Frontiers in Medicine, 2023)
Background Several clinical trials of corticosteroids have been carried out in the treatment of septic shock, however, the therapeutic effect of the most widely used hydrocortisone is still controversial, and no studies have directly compared hydrocortisone versus hydrocortisone plus fludrocortisone for patients with septic shock. Methods Baseline characteristics and treatment regimens of patients with septic shock treated with hydrocortisone from the Medical Information Mart for Intensive Care-IV database were collected. Patients were divided into hydrocortisone treatment groups and hydrocortisone plus fludrocortisone treatment groups. The primary outcome was 90-day mortality, and secondary outcomes included 28-day mortality, in-hospital mortality, length of hospital stay, and length of intensive care unit (ICU) stay. Binomial Logistic regression analysis was performed to identify independent risk factors for mortality. Survival analysis was performed and Kaplan–Meier curves were drawn for patients in different treatment groups. Propensity score matching (PSM) analysis was performed to reduce bias. Results Six hundred and fifty three patients were enrolled, of which 583 were treated with hydrocortisone alone, and 70 with hydrocortisone plus fludrocortisone. After PSM, 70 patients were included in each group. The proportion of patients with acute kidney injury (AKI) and the proportion of renal replacement therapy (RRT) treatment in the hydrocortisone plus fludrocortisone group were higher than those in the hydrocortisone alone group, and there was no significant difference in other baseline characteristics. Compared with hydrocortisone alone, hydrocortisone plus fludrocortisone did not reduce the 90-day mortality (after PSM, relative risk/RR = 1.07, 95%CI 0.75–1.51), 28-day mortality (after PSM, RR = 0.82, 95%CI 0.59–1.14) and in-hospital mortality (after PSM, RR = 0.79, 95%CI 0.57–1.11) of the enrolled patients, nor did it affect the length of hospital stay (after PSM, 13.9 days vs. 10.9 days, p = 0.34) and ICU stay (after PSM, 6.0 days vs. 3.7 days, p = 0.14), and the survival analysis showed no statistically significant difference in the corresponding survival time. After PSM, binomial Logistic regression analysis showed that SAPS II score was an independent risk factor for 28-day morality (OR = 1.04, 95%CI 1.02–1.06, p < 0.01) and in-hospital morality (OR = 1.04, 95%CI 1.01–1.06, p < 0.01), while hydrocortisone plus fludrocortisone was not an independent risk factor for 90-day mortality (OR = 0.88, 95%CI 0.43–1.79, p = 0.72), 28-day morality (OR = 1.50, 95%CI 0.77–2.91, p = 0.24), or in-hospital morality (OR = 1.58, 95%CI 0.81–3.09, p = 0.18). Conclusion In the treatment of patients with septic shock, hydrocortisone plus fludrocortisone did not reduce 90-day mortality, 28-day mortality, and in-hospital mortality compared with hydrocortisone alone, and had no effect on the length of hospital stay and ICU stay.